The Phonological Analysis of Russian Accent in the Way Back Movie by Peter Weir - Ahmad Zulfikar Adi Darma; Siti Nurani (JEdu: Journal of English Education, 2021)
Many speakers around the world have their own way in pronouncing English words as International language. The unique way in pronouncing English words is called accent. This research aims at analyzing the deviances on segmental vowel quality and quantity made by the Russian speaker in The Way Back movie by Peter Weir regarding to English short and long vowels in Russian accent. The research method was descriptive qualitative method. The research data was collected from converted audio of The Way Back Movie by Peter Weir. The data was then trimmed, selected and extracted by Praat software analysis. The results show that the Russian speaker makes deviances in pronouncing English vowel quality and vowel quantity. The total amount of deviances is 169 deviances which are divided into three classifications; those are segmental vowel quality, combinatorial quality and segmental vowel quantity deviances. The deviance that is mostly made by the Russian speaker is segmental vowel quality deviance, whereas the deviance that is rarely made by the Russian speaker is combinatorial vowel quality.